(untitled) (Jurnal Online Pertanian Tropik, 2017)
The endophytic bacteria is one of the microbes that can be used as a biofertilizer to enhance the growth and production of chili. The aim of research to determine the effectivity of endophytic bacteria as biofertilizer origin of chili and corn to increase the growth and production of chili. The experiment was conducted at home of gauze, Langsa Aceh. The research method is a randomized block design with 19 treatment and 3 replication. The results showed that isolates A1 (from roots chili) and A20 (from the roots of corn) were effective against root growth, while the A24 isolates (from corn stalks) are effective against plant height and chili.